The Implementation of Chatting as the Medium in Cyber Group Counseling - Fithriyana, Arina (IAIN Kudus, 2022)
The Implementation of Chatting as the Medium in Cyber Group Counseling. The purpose of this study is to find out an overview of the implementation of cyber group counseling through chat media, the advantages of cyber group counseling through chat media, and the obstacles or disadvantages of using chat media in the implementation of online group counseling. This research was carried out on the basis of the need to develop guidance and counseling services, especially group counseling services in the digital era. This research uses qualitative descriptive analysis method. The research setting was carried out in the Islamic Education Guidance and Counseling Study Program, Faculty of Tarbiyah IAIN Kudus in the even semester of the 2020/2021 academic year. The subject of this study is a student of the Islamic Education Guidance and Counseling study program, Faculty of Tarbiyah IAIN Kudus semester IV who took the Group Counseling course in the even academic year 2020/2021. The focus of this research is to find out an overview of the implementation of cyber group counseling through chat media. The authors used two data sources in this study, namely primary data and sequence data. Primary data were obtained through observations and interviews with respondents who practiced cyber group counseling. Meanwhile, secondary data were obtained through documentation studies/literature studies from literature books and scientific articles in journals related to the focus of this research. Data analysis is carried out through three stages, namely data reduction, data presentation, and conclusion drawing. The result is that the implementation of cyber group counseling through chat media is carried out through four stages, namely the formation stage, the transition stage, the activity stage, and the termination stage. In this case, the group leader and group members exchange conversations with each other by writing down text messages in the group chat room. The advantage of implementing cyber group counseling through chat media is that it can provide speaking opportunities to group members who are less comfortable if they convey their problems or opinions directly, and are considered more practical, efficient, and flexible in their implementation. The disadvantages are the presence of unstable signal network constraints, group dynamics are not well formed, group leaders have difficulty seeing the expressions of group members because group members' expressions are limited to the use of emoticons, and require a lot of time to write down conversations via text messages.Keywords: Cyber Group Counseling, Chat Media